A comparative polysomnography analysis of sleep in healthy controls and patients with chronic fatigue syndrome. Issue 2 (2nd April 2016) - Gotts, Zoe M.; Deary, Vincent; Newton, Julia L.; Ellis, Jason G.
ABSTRACT: Background : Sleep disturbance affects almost 95% of people with chronic fatigue syndrome (CFS). However, existing studies of sleep in CFS have shown mixed results and methodological issues prevent between-study comparisons. Purpose : To redress this, the present study aimed to investigate whether there are differences in the sleep of patients with CFS and healthy controls, using a comparative analysis of polysomnography over three consecutive nights. Methods : Twenty-two patients with CFS (1994 Centers for Disease Control and Prevention criteria) and 22 healthy controls underwent three nights of polysomnographic sleep assessment. Groups were compared on their objective sleep variables derived from the third night of assessment, to allow for participant adaptation to the sleep study. Results : 9.1% of patients met criteria for an objectively verifiable sleep disorder. Differences in sleep were observed between CFS patients and healthy controls on four objectively derived sleep variables (wake after sleep onset, sleep efficiency, percentage wake and REM Latency). In addition, people with CFS reported more severe symptoms of insomnia than healthy controls. Conclusions : The study reports on key differences in sleep between people with CFS and healthy individuals. The potential presence of a sleep disorder in this patient population is high, it is therefore important that during early evaluation, a detailed history of sleep is taken to rule out a sleep disorder in CFS. In addition, patients with CFS show poorer sleep as defined by objectively derived measures and also self-report poorer quality sleep. Improving sleep is a potential treatment target in CFS.